Ni catalysts deposited on carbon tissue prepared by pulsed laser deposition for electro-oxidation of urea - Ma, Mengying (2022)
In this work, we propose the use of carbon tissue (CT) as support for nickel nanoparticles and for single atoms as a catalyst for electro-oxidation of urea. This process can be applied in the treatment of contaminants and wastewater, in addition can produce hydrogen. The materials were prepared by pulsed laser deposition using different deposition times. 20 s, 40 s and 60 s were used for nickel nanoparticles deposition and 5 s, 10 s and 20 s were the time for nickel single atoms deposition. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to characterize the samples. The electro-oxidation reaction of urea on Ni/CT electrode in KOH solution was studied by cyclic voltammetry, chronoamperometry and electrochemical impedance spectroscopy. The results show that the nickel nanoparticles electrocatalyst with a deposition time of 20 s has less agglomeration and has more active sites. The highest peak current density was shown in the cyclic voltammetry (CV) and chronoamperometry (CA) when normalized by electroactive surface area (ESA). However, 60 s of nickel nanoparticle catalysts obtained the highest current density normalized by electrode geometric surface area (GSA), the fastest electron transfer capability verified by Electrochemical Impedance Spectroscopy (EIS), thus obtaining the best catalytic activity in practical applications. The nickel single atom electrocatalyst with deposition time of 5 s shows less aggregation, exposing more surface area and leading to higher current density. Also, the highest current density was obtained for those catalysts normalized by electrode geometry surface area. All electrodes showed good catalytic stability, which was verified by chronoamperometry (CA). The results suggest that the CT - a cheap, flexible and environmentally friendly option - can be used as a support for nickel nanoparticles and nickel single atoms during urea electro-oxidation